Numerical Simulation on Selection of Optimal Delay Time for Precise Delay Blasting - Jun Ma; Xianglong Li; Jianguo Wang; Qiang Li; Ting Zuo; Xiao Wu; Meng Hou (Shock and Vibration)
In the traditional presplitting blasting, the presplit holes are generally uniformly initiated, which causes local damage to the retained rock mass while forming the damping ditch. In order to determine the optimal delay time of the precise delay initiation hole by hole, the finite element software ANSYS/LS-DYNA is used to build a blasting model of the concrete, which includes concrete, explosive, and air to simulate the crack forming process of the presplitting hole under various initiation modes. Four kinds of initiation modes for blasting, namely, simultaneous initiation with 0 ms, 9 ms, 12 ms, and 15 ms of delay between adjacent holes, are set up to determine the exact delay time of the best presplitting effect. The simulation results show that when the prehole detonates simultaneously, the inner hole crack penetrates the fastest, but the peak stress around the hole is up to 147.9 MPa. When interhole delayed initiation is used, although the time of interhole crack penetration is prolonged, the stress coupling is generated around the precrack and the maximum stress is obviously reduced. The maximum stress generated under the three delayed initiation conditions is only 76.8 MPa. Considering the requirement of damage control of surrounding rock mass and the rapid formation of precrack, 9 ms delay time is determined as the precise delay time of this test.